A phasin with extra talents: A polyhydroxyalkanoate granule associated protein has chaperone activity - Mezzina, Mariela Paula (2015)
Phasins are proteins associated to intracellular polyhydroxyalkanoate granules that affect polymer accumulation and the number and size of the granules. Previous work demonstrated that a phasin from Azotobacter sp FA-8 (PhaPAz) had an unexpected growth-promoting and stress-protecting effect in Escherichia coli, suggesting it could have chaperone-like activities. In this work, in vitro and in vivo experiments were performed in order to investigate this possibility. PhaPAz was shown to prevent in vitro thermal aggregation of the model protein citrate synthase and to facilitate the refolding process of this enzyme after chemical denaturation. Microscopy techniques were used to analyse the subcellular localization of PhaPAz in E.coli strains and to study the role of PhaPAz in in vivo protein folding and aggregation. PhaPAz was shown to colocalize with inclusion bodies of PD, a protein that aggregates when overexpressed. A reduction in the number of inclusion bodies of PD was observed when it was coexpressed with PhaPAz or with the known chaperone GroELS. These results demonstrate that PhaPAz has chaperone-like functions both in vitro and in vivo in E.coli recombinants, and suggests that phasins could have a general protective role in natural polyhydroxyalkanoate producers.